Ageless harmony: decoding the microbiome–stem cell nexus in aging - Swarup K. Chakrabarti; Dhrubajyoti Chattopadhyay (Academia Molecular Biology and Genomics)
The dynamic interplay between aging stem cells and the microbiota is a burgeoning frontier in biomedical science, unveiling key insights into systemic health maintenance. Among the myriad microbial communities inhabiting the human body, the gut microbiome emerges as a pivotal regulator, heavily influencing stem cell function through the production of an array of bioactive substances, including vitamins, secondary metabolites, and short-chain fatty acids. Delving into these microbial influences reveals their multifaceted effects on various facets of stem cell biology, such as maintenance, proliferation, and differentiation. Together these interactions shape tissue regeneration and repair highlighting the key role of the microbiota in orchestrating cellular homeostasis. Dysbiosis, marked by age-related changes in gut microbiota composition, disrupts the signals necessary for optimal stem cell activation. As a result, tissue regeneration becomes affected, resulting in reduced capacities for repair and renewal with aging. Techniques, such as spatial transcriptomics and single-cell sequencing, provide opportunities to unravel the molecular intricacies underpinning the crosstalk between gut microbes and stem cells within their tissue microenvironments, thereby governing health and longevity. While therapeutics targeting the microbiome hold promise in keeping stem cell homeostasis and tissue repair capacities, the primary focus remains on deepening our understanding of the interplay between the microbiota and stem cells. Such insights not only illuminate age-related decline but also hold great implications for improving human health, which in turn paves the way for newer treatments while laying the groundwork for a deeper evaluation of the microbiome–stem cell axis and its impact on diverse physiological processes.